Mineralogy and fluid inclusions investigation of the conglomerate-hosted Gharmorvarid occurrence, Southwest Arak, Iran - Zahra Alaminia (Journal of Stratigraphy and Sedimentology Researches)
AbstractThe Gharmorvarid ore occurrence in southwest Arak, Iran, is located within the Malayer–Isfahan metallogenic province, which is hosted by a basal conglomerate of the Early Cretaceous sedimentary strata. Mineralization consists of galena and pyrite with trace amounts of chalcopyrite and sphalerite. Ore occurs as disseminated, replacement, mottled, and space-filling style. The gangue is dominated by quartz, ankerite, siderite, Fe-dolomite, calcite, sericite, biotite, chlorite, and minor barite. Our findings indicate a sequence of events during ore formation: euhedral quartz and fine-grained sulfide minerals are hosted within earlier diagenetic carbonate, galena with pervasive Fe-Mg-Mn-carbonate alteration occurred after them, leading to the dissolution (replacement) reaction in contact with quartz. Later minerals are characterized by coarse-grained quartz, galena, sericite, biotite, and chlorite. Primary fluid inclusions trapped in quartz and dolomite reveal that ore-forming fluid was intermediate saline, with a range from 3.7 to 16.2 wt % NaCl equiv. and had a medium to high temperature ranging from 151 to 330 ºC. The mineralization is controlled by a fault-fold structure. The Gharmorvarid mineralization is very similar to the sandstone-hosted Pb-Zn deposits along the margin of the Scandinavian Caledonides and in particular the Laisvall deposit in Sweden.Keywords: Conglomerate, Lead mineralization, SEM, Fluid inclusions, Arak.  IntroductionIn comparison to lead-zinc deposits hosted by shales and limestones, few are located in sandstones and conglomerates. As a result, global demand for imbalanced mineral resources, such as conglomerate-hosted Pb-Zn deposits, has gradually increased. Recently, a large Pb-Zn deposit (Uragen) was discovered in China hosted by sandstones and conglomerates (Gao et al., 2022). In Iran, a notable concentration of lead and zinc deposits, along with mineral occurrences, is observed in the Lower Cretaceous sediments south of Arak. From a stratigraphic perspective, ore-bearing horizons are deposited in shale-carbonate units of the Cretaceous except for two mineral occurrences, Dokhaharan and Gharmorvarid, which are hosted in the Cretaceous basal conglomerates (Momenzadeh, 1976; Mahmoodi et al., 2021). Although numerous economic, geological studies have been conducted on the Arak deposits, no investigation has thus far focused specifically on the conglomerate-hosted Gharmorvarid deposit. This presents a promising opportunity for us to explore further. Material & MethodsAfter examining the geological map, samples were collected from the mineralized outcrops and the host rock. Thin sections of all samples were studied by transmitted and reflected microscopy in the Economic Geology laboratory at the University of Isfahan. To identify the surface morphology and chemical composition, the samples were carbon-coated and examined with a Scanning Electron Microscope (SEM). Microthermometric measurements were carried out at the University of Isfahan using the Linkam THM600. The samples used all drive from the two host mineral phases of carbonate and quartz from the Gharmorvarid. Discussion of Results & ConclusionsThe Gharmorvarid anticline is situated approximately 7 kilometeres northeast of the Emarat. The stratigraphic successions of Gharmorvarid consist of two sedimentary strata including the Jurassic and the Cretaceous. The oldest rocks consist of medium-bedded sandstones, which has been overlain by the basal conglomerates of the Early Cretaceous. These sedimentary rocks are tectonically folded. Mineralization was controlled by the thrust systems and occurred within the conglomerates. The Conglomerate ranges from quartz arenite to subgreywacke, composed of grains consisting mainly of quartz, chert, lesser carbonates, opaque, and accessory minerals. This unit preserves evidence of two types of alteration: diagenetic and hydrothermal. Diagenetic processes have increased porosity and permeability, providing a suitable structure for the ore-bearing fluid flows. The major ore types of the Gharmorvarid are disseminated, replacement, semi-massive, and open space filling. The ore mineral is mainly coarse-grained galena. The common gangue minerals are quartz, Fe-Mg-Mn carbonates, pyrite, minor chlorite, sericite, and biotite.A number of fluid inclusions in quartz and carbonate minerals were measured for Th, which was found to range from 133 to 323 ºC. The salinity calculated from the final ice melting temperature was observed in the range of -2.2 to -12.3 ºC. These temperatures correspond to salinities ranging from 5.1 to 39.5 eq. wt.%.The Gharmorvarid ore occurrence is controlled by a fault-fold structure. The sedimentary succession of Gharmorvarid indicates that from the onset of deposition of the Early Cretaceous strata, the sedimentary basin exhibited a tendency towards subsidence and deepening. Mineralogical observations of the host rock suggest that the succession was deposited in a shallow coastal environment, which was influenced by diagenesis. However, in the upper horizons, which predominantly consist of carbonate sediments containing outlined features, there is evidence of basin deepening and the activity of syn-sedimentary faults. The results of this study align with the tectonic events of the Sanandaj–Sirjan zone and clearly demonstrate the transition in the tectonic regime from extensional to compressional. Therefore, it is proposed that, alongside basin subsidence during diagenesis, conditions were favorable for the mineralization in Gharmorvarid. During the orogeny in the Late Cretaceous, the faults were reactivated, and ore-bearing fluids migrated from deeper parts to shallow zones within the conglomerate unit through steep reverse faults. Consequently, the main mineralization was deposited between the particles of the host rock in Gharmorvarid due to mixing with seawater and intraformational fluids.